One mile under ebook A ty hauck novel. - Gross, Andrew (Ty Hauck., 2015)
In New York Times bestselling author Andrew Gross's propulsive thriller, set amid the drought-stricken oil country of Colorado's beautiful high plains, Ty Hauck makes his long-awaited return rallying beaten-down farmers and ranchers against a giant energy company in a deadly confrontation involving murder, retaliation, and cover-up. Leading a tour down the rapids outside Aspen, Colorado, whitewater guide Dani Whalen comes upon the dead body of a close friend. Trey Watkins's death is ruled an accident. Finding evidence that seems to back up her suspicions that it wasn't, she takes her case to Wade Dunn, the local police chief and her ex-stepfather, with whom she shares some unresolved history. Wade insists the case is closed, but Rooster, a hot air balloon operator in town, claims he saw something from the air she should know. When he suddenly dies in a fiery crash, Dani threatens to take her suspicions public, goading Wade into tossing her in jail. When an old friend contacts Ty Hauck and says his daughter is in trouble, he doesn't hesitate to get involved. Together, the two step into a sinister scheme running deep beneath the surface of a quiet, Colorado town that has made a deal with the devil to survive. But in the square off between giant energy companies and beaten-down ranchers and farmers, one resource is even more valuable in this drought-stricken region than oil. They both will kill for it—water. One Mile Under is a thrilling rapid run of hair-raising twists and unforeseen turns set against one of the most provocative environmental issues of our time.